Making space for bi+ identities : explorations of genders, identities, and relationships - Nelson, Rosie (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"How do bi+ people navigate identity, gender, and relationships in a biphobic society? This book explores this question to show how to better include and incorporate bi+ people in research, policy, and the everyday. You can expect this book to explore how bi+ people experience the gender binary, healthcare, sex, flirting, media representation, and research. It soon becomes clear that bi+ people have different needs and experiences than heterosexual, lesbian, and gay people, and so need specific inclusion measures. Further, the research explores bi+ people's nuanced approaches to understanding gender, sexuality, sex, and flirting. This book will be of interest to anyone, whether bi+, a student, a researcher, a policymaker, or a health worker develop their understanding of bi+ identities and needs. It will also be of interest to people interested in a broad range of topics, including sexuality, gender, feminism, trans and non binary identities, LGBTQ+ topics, and everyday sociology"--
Keywords: Bisexuals; Sexual minorities -- Identity; Gender identity; SOCIAL SCIENCE / Sociology / General